A Matching-Adjusted Indirect Comparison of Sonidegib and Vismodegib in Advanced Basal Cell Carcinoma - Dawn Odom; Deirdre Mladsi; Molly Purser; James A. Kaye; Eirini Palaka; Alina Charter; Jo Annah Jensen; Dalila Sellami (Journal of Skin Cancer)
Objectives. Based on single-arm trial data (BOLT), sonidegib was approved in the US and EU to treat locally advanced basal cell carcinomas (BCCs) ineligible for curative surgery or radiotherapy. Vismodegib, the other approved targeted therapy, also was assessed in a single-arm trial (ERIVANCE). We examined the comparative effectiveness of the two drugs using a matching-adjusted indirect comparison (MAIC) versus an unadjusted indirect comparison. Methods. After comparing trials and identifying potential prognostic factors, an MAIC was conducted to adjust for differences in key patient baseline characteristics. Due to BOLT’s small sample size, the number of matching variables was restricted to two. Efficacy results for sonidegib were generated so that selected baseline characteristics matched those from ERIVANCE and were compared with published ERIVANCE results. Results. Matching variables were baseline percentages of patients receiving prior radiotherapy and surgery. After weighting, sonidegib objective response rate (ORR) and median progression-free survival (PFS) were effectively unchanged (prematched versus postmatched ORR and PFS, 56.1% versus 56.7% and 22.1 versus 22.1 months, resp.). Vismodegib’s ORR and PFS were 47.6% and 9.5 months. Conclusions. Comparative effectiveness of sonidegib versus vismodegib remains unchanged after adjusting BOLT patient-level data to match published ERIVANCE baseline percentages of patients receiving prior surgery and radiotherapy.